Optimizing Kahoot! Platform As Digital Media To Increase The Students’ Interest And Motivation In Learning English (Case Study At English As General Subject In STIE Enam Enam Kendari) - Yuditra Farmana; Almansyah Rundu Wonua (CV. Inara, 2021)
This research was conducted based on the problem statement that English subject was considered as an irrelevant and not interesting subject for bachelor program of management students as non-English students in STIE Enam Enam Kendari. Based on pre-observation using a questionnaire, many students had difficulties in learning English because of the lack of interest and afraid to participate in the learning process. The aims of this research were (1) Identifying the factors which affected the students' interest and active learning (2) Developing digital learning media to engage the students' interest and motivation by optimizing one of the game-based learning platforms namely Kahoot!. The result showed (1) Some factors affected the students’ interest and motivation in learning English. There were 30 students with the lowest interest and motivation in learning English selected as the sample of the research to be interviewed and assessed by using likert scale. Some of them answered that classroom atmosphere and teaching methods used by the teachers made them felt bored and anxious. (2) Optimizing Kahoot! platform as digital learning media was the appropriate way to increase the students' interest and motivation in learning English. The researcher used Kahoot! platform to complete the lesson plan that has been arranged before entering the class. Even, Kahoot! was used to test the students in the final examination. After applying Kahoot! platform as digital learning media, 30 students gave positive responses and considered that Kahoot! could create a fun and interactive learning process in the classroom. They felt happy and excited when following the English class.